Editorial - Levent ÖZÇAKAR, (Archives of Rheumatology, 2014)
Dear Authors and Readers, Of the eight original articles published in this issue of the Arch Rheumatol, three pertain to research on basic (genetic) sciences in Henoch Schönlein purpura, rheumatoid arthritis, and familial Mediterranean fever. Furthermore, our content is enriched by two clinical studies on neuropsychiatric manifestations of systemic lupus erythematosus and pregnancy outcomes of familial Mediterranean fever patients. Additionally, we have imaging studies on early hip joint involvement in ankylosing spondylitis and peripheral nerve problems. Interesting case reports exemplifying rare scenarios of systemic sclerosis, Wegener's granulomatosis, and other musculoskeletal conditions will add more backbone to this issue. We hope you will enjoy reading it. On behalf of the editorial team, Yours sincerely, Levent Özçakar, MD, Professor Editor-in Chief, Arch Rheumatol